The Development of Integration Theories in Ukraine - Fedinec, Csilla (The Development of European and Regional Integration Theories in Central European Countries, 2022)
In the following, we cite the first lines of the preamble of the Constitution of Ukraine (1996): ‘The Verkhovna Rada of Ukraine, on behalf of the Ukrainian people—citizens of Ukraine of all nationalities, expressing the sovereign will of the people, based on the centuries-old history of Ukrainian state- building…’. The function of the preamble is to summarize the purpose of the legislator. These cited lines of the preamble of the Ukrainian constitution have not changed since it was adopted, placing the state idea first. It has public legal, historical, and symbolic meanings; at the same time, the Ukrainian territories for several decades formed peripheries of larger state units that could not be legally separated. The administrative boundaries of the country were accepted only in the 20th century, and the country became independent only in 1991. The periods of decisive significance concerning the Ukrainian national idea and the independent state were the following: the first East Slavic state, the Kyivan Rus’; from Slavic vassals of the Golden Horde medieval regions of Galicia and Volhynia, the Cossack Age (Zaporizhian Host); the period of the Ukrainian national revival in the 19th century; the period of the Ukrainian People’s Republic following the First World War; the Soviet Ukraine, when the borders of the present state were established; and the establishment of the present independent Ukrainian state.KEYWORDS: Ukraine, history, federalization, autonomy, national movement, independent statehood, integration development.